(untitled) (CIPEEX, 2022)
AGING IS A PROGRESSIVE AND IRREVERSIBLE FACTOR THAT DEALS WITH A GRADUAL PROCESS OF MOTOR AND SENSORY LOSSES OVER TIME. ONE OF THE FUNDAMENTAL PROCESSES OF AGING IS THE REDUCTION OR LOSS OF FUNCTIONAL STRENGTH, WHICH DIRECTLY AFFECTS THE ABILITY AND PRACTICE OF DAILY LIFE ACTIVITIES. TO UNDERSTAND THE INFLUENCE OF FUNCTIONAL CAPACITY AS AN INDICATOR ON THE QUALITY OF LIFE OF THE ELDERLY. A SAMPLE OF 20 ELDERLY (71.65 ± 3.63 YEARS) WERE SUBMITTED TO THE QUALITY OF LIFE QUESTIONNAIRE (SF-36), THE SIX-MINUTE WALK TEST AND THE ONE-MINUTE SIT-TO-STAND TEST, BEING CONSIDERED FOR ANALYSIS PURPOSES THE VALUES €‹€‹OBTAINED IN EACH TEST AND QUESTIONNAIRE. ELDERLY PEOPLE WITH LIMITATIONS IN PERFORMING THE PROPOSED TESTS, SYSTOLIC BLOOD PRESSURE 150 MMHG OR DIASTOLIC BLOOD PRESSURE 100 MMHG, HEART RATE < 50 BPM, AND ELDERLY PEOPLE WHO REFUSED TO SIGN A TERM (ICF) WERE EXCLUDED. BEFORE PERFORMING EACH TEST, THE ELDERLY WERE INSTRUCTED TO REMAIN AT REST FOR 10 MINUTES, SOON AFTER, BLOOD PRESSURE, SATURATION AND HEART RATE WERE MEASURED AND RECORDED, LATER THE TESTS WERE STARTED, AT THE END OF EACH TEST, THE SCALE OF BORG FOR DYSPNEA AND MUSCLE FATIGUE. IN EACH TEST, AN EVALUATOR STAYED CLOSE TO THE ELDERLY PERSON TO PROMOTE SAFETY IN CASE OF IMBALANCE, THE ELDERLY WERE INSTRUCTED THAT THEY SHOULD INFORM IF THEY ARE NOT ABLE TO COMPLETE THE TESTS. DATES WERE EXPRESSED AS MEAN AND STANDARD DEVIATION FROM THE MEAN. INITIALLY, THE KOLMOGOROV-SMIRNOV AND SHAPIRO-WILK TEST WAS PERFORMED TO VERIFY THE NORMALITY OF THE DATA. PEARSON’S CORRELATION WAS USED TO VERIFY HOW MUCH THE WALK TEST WAS RELATED TO THE SIT AND STAND TEST, AND THE SPEARMAN’S CORRELATION TO VERIFY THE CORRELATION BETWEEN THE DOMAINS OF THE QUALITY OF LIFE QUESTIONNAIRE AND THE TESTS. THE DATA WERE PROCESSED USING THE SPSS STATISTICAL PROGRAM. SCALE OF SUBJECTIVE PERCEPTION OF EFFORT AND MUSCULAR FATIGUE (BORG) ESTIMATED AT THE END OF THE SIT-TO-STAND TEST WAS SIGNIFICANTLY HIGHER THAN AT THE END OF THE SIX-MINUTE WALK TEST. IN THE PRESENT STUDY, THERE WAS NO CORRELATION BETWEEN THE DISTANCE COVERED IN THE SIX-MINUTE WALK TEST AND THE NUMBER OF REPETITIONS IN THE SIT-AND-STAND TEST. HOWEVER, THERE IS A STRONG CORRELATION BETWEEN THE DISTANCE COVERED IN THE 6-MINUTE WALK TEST AND THE DOMAIN OF SOCIAL ASPECTS AND VITALITY, THERE IS ALSO A MEDIAN CORRELATION BETWEEN FUNCTIONAL CAPACITY AND LIMITATION DUE TO PHYSICAL ASPECTS AND MENTAL HEALTH. HOWEVER, THE NUMBER OF REPETITIONS OF THE 1-MINUTE SIT-AND-STAND TEST HAS A MODERATE CORRELATION WITH THE DOMAIN OF FUNCTIONAL CAPACITY, GENERAL HEALTH STATUS AND SOCIAL ASPECTS. IT IS CONCLUDED THAT IT IS NOT POSSIBLE TO SAY THAT ONE TEST CAN REPLACE THE OTHER. HOWEVER, RESULTS OBTAINED IN THE PRESENT STUDY SUGGEST THAT QUALITY OF LIFE IS CAPABLE OF IMPROVING FUNCTIONAL CAPACITY IN THE ELDERLY POPULATION.